Implementasi Pendekatan Konstruktivistik Dalam Collaboration Skill Pendidikan Agama Islam Di Kurikulum Merdeka - Fenty, Ismi; Harmi, Hendra; Amrullah, Amrullah (Universitas Majalengka, 2024)
This study analyzes the implementation of a constructivistic approach in the development of collaboration skills in Islamic Religious Education subjects in the Independent Curriculum at SD Alam Insan Mulia Lubuklinggau. With a qualitative descriptive method, data was obtained through observation, interviews, and document analysis using purposive sampling techniques. The results of the study show that the Independent Curriculum allows a constructivistic approach to develop, especially through groupwork and discussion-based learning that improves students' collaboration, engagement, and motivation skills. This approach is also effective in integrating the nature school curriculum and encouraging the development of social, emotional, and critical and creative thinking skills. However, the study found weaknesses, such as adaptation difficulties for students who prefer to learn individually or lack confidence in cooperation.